Characterizing the Effect of Cytochrome P450 (CYP) 2C8, CYP2C9, and CYP2D6 Genetic Polymorphisms on Stereoselective N‐demethylation of Fluoxetine. Issue 3 (24th January 2014) - Wang, Zhangting; Wang, Shengjia; Huang, Minmin; Hu, Haihong; Yu, Lushan; Zeng, Su
ABSTRACT Fluoxetine (FLX) is one of the most widely prescribed selective serotonin reuptake inhibitors. Although FLX is used as racemate in the clinic, the clinical pharmacokinetics of FLX and its N‐demethylation metabolite norfluoxetine (NFLX) show obvious cytochrome P450 (CYP) polymorphism dependency and exhibit marked stereoselectivity. However, the kinetic profiles of CYP variants to FLX remain unclear. In the present study, some variants of human CYP2C8, CYP2C9, and CYP2D6 were first expressed in insect cells, and their catalytic roles with respect to FLX enantiomers were then investigated. CYP2C8.4 and CYP2C9.10 showed significantly lower activity and CYP2C8.3 showed significantly higher activity toward both R‐ and S‐FLX compared with the wildtype, while CYP2C9.3, CYP2C9.13, and CYP2C9.16 showed significantly lower activity only toward R‐FLX. Five CYP2C9 variants and CYP2D6.1 exhibited significantly stereoselective kinetic profiles prior to R‐FLX, and CYP2C8.3 showed a slight stereoselectivity. Interestingly, obvious substrate inhibition was observed in the CYP2C9 wildtype and its three variants only in the case of R‐FLX. Together, these findings suggest that CYP2C9 and CYP2D6 polymorphism may play an important role in the clearance of FLX and also in the stereoselective kinetic profiles of FLX enantiomers. Chirality 26:166–173, 2014. © 2014 Wiley Periodicals, Inc.